2007
DOI: 10.1002/hbm.20408
|View full text |Cite
|
Sign up to set email alerts
|

Mouse behavioral mutants have neuroimaging abnormalities

Abstract: Impaired cognitive, memory, or motor performance is a distinguishing characteristic of neurological diseases. Although these symptoms are frequently the most evident in human patients, additional markers of disease are critical for proper diagnosis and staging. Noninvasive neuroimaging methods have become essential in this capacity and provide means of evaluating disease and tracking progression. These imaging methods are also becoming available to scientists in the research laboratory for assessment of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…In a recent study of mice with heritable mutations that display behavioral symptoms, 87% of these strains showed neuroimaging abnormalities including volumetric changes using high resolution MRI [Nieman et al, 2007]. In keeping with this finding, Magel2-null mice have brain abnormalities that we detected by MRI.…”
Section: Magel2-null Mice Have Reduced Brain Volume and Reduced Neurosupporting
confidence: 85%
“…In a recent study of mice with heritable mutations that display behavioral symptoms, 87% of these strains showed neuroimaging abnormalities including volumetric changes using high resolution MRI [Nieman et al, 2007]. In keeping with this finding, Magel2-null mice have brain abnormalities that we detected by MRI.…”
Section: Magel2-null Mice Have Reduced Brain Volume and Reduced Neurosupporting
confidence: 85%
“…Had those studies been performed on the same animals, that is, behavioral testing of the animals with either in vivo imaging concurrently and/or ex vivo imaging after sacrifice, it is likely that there would be even more consistency. In a previous report, both behavioral and neuroanatomical phenotypic outcomes were detected in 17 of 19 different mouse models [155]. To build upon this further, it has been shown that behavioral training can directly influence the neuroanatomy.…”
Section: Large-scale Discovery (2014)mentioning
confidence: 88%
“…Radiation treatment in mice also results in behavioral abnormalities, including impaired learning and memory that has been associated with reduced hippocampal neurogenesis (17)(18)(19). As may be expected (20,21), anatomical changes through development are also present (22) with a dependence on age, dose, and sex (23), reminiscent of known risk factors in human patients (9,24).…”
Section: Introductionmentioning
confidence: 99%